Daya Hambat Staphylococcus Aureus Terhadap Ekstrak Metanol Daun Sirsak (Annona Muricata L.) - Amjad Mohammad Nadlif; Muhammad walid (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The use of antibiotics can cause drug resistance if their use is not appropriate, so alternative treatment from plants is needed, one of which is soursop leaves (Annona muricata L.). Chemical substances contained in soursop leaves can prevent development until they can kill bacteria, one of which is flavonoids. The purpose of this study was to determine whether soursop leaf methanol extract (Annona muricata L.) at concentrations of 25%, 50%, 75% can inhibit the growth of Staphylococcus aureus bacteria and can determine at what concentration soursop leaf extract (Annona muricata L.) can effectively inhibit Staphylococcus aureus. The simplisia extract was done by maceration strategy using methanol as a solvent. The antibacterial testing method uses the disc diffusion method and uses clindamycin as a positive control and distilled water as a negative control. The results showed that Annona muricata L. extract can provide antibacterial action at concentration variants of 25%, 50% and 75% which is characterized by the presence of transparent areas with an average diameter of 8.97mm, 11.36 mm and 13.3mm respectively with positive control with a diameter of 23.25 and negative control with a diameter of 0 mm. Soursop leaf methanol extract (Annona muricata L.) is able to suppress the growth of Staphylococcus aureus bacteria with the most effective concentration variant of 75%.